The importance of knowing the starting level of knowledge - R. Barajas; P. Saavedra; J. Albéniz; I. Carrillo (Multidisciplinary Journal for Education, Social and Technological Sciences)
The aim of this work is to demonstrate the importance of the fact that from the beginning of the course students and teachers identify what is the initial knowledge level and the level that students must reach at the end of the course. This is important for the student because it will demonstrate the importance of the continuous assessment (Bologne methodology) and in the other hand, for the teachers to know the initial level of their students. It can give influence to detect deficiencies and solve them to a well ending course. This helps a lot to students with an initial lack of knowledge of the subject. This study carries out specifically in the Chemistry subject in the degree of Ingeniería de Diseño Industrial y Desarrollo de Producto (Industrial Design Engineering and Product Development) at Escuela Universitaria de Ingeniería Técnica Industrial (E.U.I.T.I.) of the Universidad Politécnica de Madrid (UPM).